Utilization of the PCR technique for identifying post-surgical infections at Rzgari Hospital in Erbil - Khorsheed, Shler (Nursing and Health Sciences Journal (NHSJ), 2025)
Contaminated surgical wounds have emerged as a significant problem in many healthcare settings, leading to prolonged hospitalization and increased treatment costs. One of the primary purposes of this research was to analyze the types of microorganisms present in all collected samples from post-surgical wounds and to assess their antimicrobial susceptibility. PCR was applied as a reliable diagnostic tool to identify the isolated microbial agents. Specimens included 110 wound swabs collected from patients aged between 10 and 55 years who had recently undergone various surgical procedures at Rzgari Hospital in Erbil, Iraq. The bacterial isolates were identified using traditional microbiological approaches, and all isolates were subjected to antibiotic resistance testing performed on all isolated species. PCR was employed to differentiate between the microbial species. The results revealed the presence of several bacterial species in surgical wound sites, with the following prevalence rates: E. coli (35.9%), S. aureus (27.8%), P. aeruginosa (24.3%), Acinetobacter spp. (9.9%), and Enterobacter spp. (9.1%). The predominant isolates demonstrated Susceptibility testing to vancomycin and amikacin. ERIC-PCR analysis was applied to 9 S. aureus and 17 E. coli isolates, revealing four distinct genetic profiles, indicating considerable genetic diversity. DNA fingerprinting images were obtained for both species. The results of this study underscore the critical role of precise microbial identification and antibiotic susceptibility testing in effectively managing postoperative wound infections. The outcomes of this research could enhance infection control strategies and support improved clinical care for patients undergoing surgery.